Intravenous thrombolysis and endovascular therapy for acute ischemic stroke in COVID-19: a systematic review and meta-analysis - Stuckart, Isabella; Kabsha, Ahmed; Siepmann, Timo; Barlinn, Kristian; Barlinn, Jessica (Frontiers in Neurology, 2023)
Background The impact of COVID-19 on clinical outcomes in acute ischemic stroke patients receiving reperfusion therapy remains unclear. We therefore aimed to synthesize the available evidence to investigate the safety and short-term efficacy of reperfusion therapy in this patient population. Methods We searched the electronic databases MEDLINE, Embase and Cochrane Library Reviews for randomized controlled trials and observational studies that investigated the use of intravenous thrombolysis, endovascular therapy, or a combination of both in acute ischemic stroke patients with laboratory-confirmed COVID-19, compared to controls. Our primary safety outcomes included any intracerebral hemorrhage (ICH), symptomatic ICH and all-cause in-hospital mortality. Short-term favorable functional outcomes were assessed at discharge and at 3 months. We calculated pooled risk ratios (RR) and 95% confidence intervals (CI) using DerSimonian and Laird random-effects model. Heterogeneity was evaluated using Cochran’s Q test and I2 statistics. Results We included 11 studies with a total of 477 COVID-19 positive and 8,092 COVID-19 negative ischemic stroke patients who underwent reperfusion therapy. COVID-19 positive patients exhibited a significantly higher risk of experiencing any ICH (RR 1.54, 95% CI 1.16–2.05, p < 0.001), while the nominally increased risk of symptomatic ICH in these patients did not reach statistical significance (RR 2.04, 95% CI 0.97–4.31; p = 0.06). COVID-19 positive stroke patients also had a significantly higher in-hospital mortality compared to COVID-19 negative stroke patients (RR 2.78, 95% CI 2.15–3.59, p < 0.001). Moreover, COVID-19 positive stroke patients were less likely to achieve a favorable functional outcome at discharge (RR 0.66, 95% CI 0.51–0.86, p < 0.001) compared to COVID-19 negative patients, but this difference was not observed at 3-month follow-up (RR 0.64, 95% CI 0.14–2.91, p = 0.56). Conclusion COVID-19 appears to have an adverse impact on acute ischemic stroke patients who undergo reperfusion therapy, leading to an elevated risk of any ICH, higher mortality and lower likelihood of favorable functional outcome. Systematic review registration PROSPERO, identifier CRD42022309785.